The Evolution of Secondary Territory, inside the Dezful Houses - Alireza Einifar; Azadeh Aghalatifi; Zeinab Hayati (صفه)
Understanding cognitive territory in physical space is one of the most basic human ‎needs. One of the contraption that the Iranian architect has used for this purpose is ‎to provide a special model for spatial division in the architecture of the building, ‎in such a way that by separating public spaces and private spaces, a quiet space is ‎provided for family members without interference. Territories can be variable in ‎time and space. Some territories are under the constant supervision and control of a ‎particular individual or group. Others are temporary and almost everyone has access ‎to it, and ultimately groups, at the same time being both available to the public and ‎under the supervision of regular people. Considering the importance of this type of ‎territory (According to Altman named secondary territory) in the home, which not only ‎provides the collective space of the family but also plays a serious role in the ‎formation of social interactions and the creation of collective memories, the ‎objective of this paper investigates the evolution of the secondary territory in the ‎houses of Dezful. The approach of this research is qualitative and the research ‎method is logical argumentation. At first, using library resources, the position of ‎the territory and its related theories have been gathered. Then Based on field ‎observations and Semi-structured deep interviews with residents, the data were ‎extracted by coding. Based on that, it became possible to recognize the real ‎boundaries of each of the three kind of territories by understanding the cultural ‎features, the ways of living and life style. Investigations in the secondary ‎territories in the houses of Dezful indicate the reduction of spatial diversity, ‎from open space, semi-open space, and closed space to a completely closed space. In ‎addition, these changes have been accompanied with reduction in habitable levels and ‎elimination of vertical communication, and increase of single functional spaces.  ‎And also the results show that during this period of time, the use of secondary ‎territories has been less dependent on time and seasons, therefore less collective ‎memories has been formed.‎